Dynamic contrast-enhanced magnetic resonance imaging of the sarcopenic muscle - Sbarbati Andrea; Lunati Ernesto; Marzola Pasquina; Asperio Roberto M; Farace Paolo; Nicolato Elena; Osculati Francesco (BMC Medical Imaging, 2002)
Abstract Background Studies about capillarity of the aged muscle provided conflicting results and no data are currently available about the magnetic resonance imaging (MRI) in vivo characteristics of the microvascular bed in aged rats. We have studied age-related modifications of the skeletal muscle by in vivo T2-relaxometry and dynamic contrast-enhanced magnetic resonance imaging (CE-MRI) at high field intensity (4.7 T). The aim of the work was to test the hypothesis that the ageing process involves microvessels in skeletal muscle. Methods The study was performed in 4-month-old (n = 6) and 20-month-old (n = 6) rats. Results At MRI examination, the relaxation time T2 of the gastrocnemius muscle showed no significant difference between these two groups. The kinetic of contrast penetration in the tissue showed that in 4-month-old rats the enhancement values of the signal intensity at different time-points were significantly higher than those found in senescent rats. Conclusion The reported finding suggests that there is a modification of the microcirculatory function in skeletal muscle of aged rats. This work also demonstrates that CE-MRI allows for an in vivo quantification of the multiple biological processes involving the skeletal muscle during aging. Therefore, CE-MRI could represent a further tool for the follow up of tissue modification and therapeutic intervention both in patients with sarcopenia and in experimental models of this pathology.